2015
DOI: 10.1159/000441683
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Potential of Resistant Starch in Modulation of Insulin Resistance, Endotoxemia, Oxidative Stress and Antioxidant Biomarkers in Women with Type 2 Diabetes: A Randomized Controlled Clinical Trial

Abstract: Aims: This trial aims to determine the effects of resistant starch (RS) subtype 2 (RS2) on glycemic status, metabolic endotoxemia and markers of oxidative stress. Methods: A randomized, controlled, parallel-group clinical trial group of 56 females with type 2 diabetes mellitus (T2DM) was divided to 2 groups. The intervention group (n = 28) and control group (n = 28) received 10 g/day RS2 or placebo for 8 weeks, respectively. Fasting blood samples were taken to determine glycemic status, endotoxin, high sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 35 publications
3
55
0
Order By: Relevance
“…The higher IGFBP-1 levels seen in those treated with CoQ10 and selenium suggest a decreased insulin response to the meal due to improved insulin sensitivity. The increased IGF-1 levels induce improved insulin sensitivity in accordance with previous studies showing that antioxidants can improve insulin sensitivity [51, 52]. Our results indicating increased insulin sensitivity are interesting in relation to previous concerns about the possibility that selenium supplementation should cause an increased risk of diabetes [53].…”
Section: Discussionsupporting
confidence: 92%
“…The higher IGFBP-1 levels seen in those treated with CoQ10 and selenium suggest a decreased insulin response to the meal due to improved insulin sensitivity. The increased IGF-1 levels induce improved insulin sensitivity in accordance with previous studies showing that antioxidants can improve insulin sensitivity [51, 52]. Our results indicating increased insulin sensitivity are interesting in relation to previous concerns about the possibility that selenium supplementation should cause an increased risk of diabetes [53].…”
Section: Discussionsupporting
confidence: 92%
“…It has been well‐reported that the oxidative stress was increased in the patients with diabetes and diabetic animals, reflected by enhanced oxidative stress biomarkers in the bloods and tissues, such as malondialdehyde, 3‐nitrotyrosine, 4‐hydroxynonenal and reactive oxygen species . The oxidative stress in the patients with T2DM may play a crucial role in the development of diabetic complications .…”
Section: Discussionmentioning
confidence: 98%
“…It is well established that by trapping water in the colon, high fiber intake can relieve constipation and improve bowel habits . In fact, increased dietary fibers has been shown to relieve constipation in diabetic patients and CKD animals . However, fermentation of fiber in the colon produces gases including hydrogen and methane which cause flatulence and abdominal discomfort.…”
Section: Discussionmentioning
confidence: 99%